Vegetable Sales and Marketing Modeling Through Innovation of Online Vegetable Stalls and Carts Based on Website and Mobile Applications - Surtikanti; Raeny Dwisanty; Andri Sahata Sitanggang (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to create an integrated system consisting of a website platform and a mobile application. This study aims to provide easy, practical and safe access to interactions and transactions between sellers and buyers of vegetables. This research method uses a qualitative approach by conducting a survey on the pattern of running vegetable sales businesses and interviews with vegetable sellers and buyers. Furthermore, analysis of design, system development and socialization to users is carried out. By implementing this online sales system, it can provide easy access to practicality and security. This research also has an impact on increasing the dynamic and sustainable economic cycle with the support of information technology.